2023
DOI: 10.3934/amc.2021022
|View full text |Cite
|
Sign up to set email alerts
|

Five-weight codes from three-valued correlation of M-sequences

Abstract: <p style='text-indent:20px;'>In this paper, for each of six families of three-valued <inline-formula><tex-math id="M1">\begin{document}$ m $\end{document}</tex-math></inline-formula>-sequence correlation, we construct an infinite family of five-weight codes from trace codes over the ring <inline-formula><tex-math id="M2">\begin{document}$ R = \mathbb{F}_2+u\mathbb{F}_2 $\end{document}</tex-math></inline-formula>, where <inline-formula><tex-math id=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…In a similar way for a trace code C L , defined through (1), let A j (0 ≤ j ≤ 2n) be the number of codewords with Lee weight j in the linear code C L of length n over R, then the Lee weight enumerator of C L , Lee C L (z), is defined by Lee C L (z) = 2n j=0 A j z j . Through different choices of the defining set L, and particularly when F q is either the binary field (F 2 ) or a prime field (F p ), several optimal or nearly optimal codes from trace codes of the form C L where recently found ( [4,5,8,9,[11][12][13][14][15][16]). Particularly, the construction of two or few-weight codes from trace codes over the ring F q + uF q , was recently presented in [4].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…In a similar way for a trace code C L , defined through (1), let A j (0 ≤ j ≤ 2n) be the number of codewords with Lee weight j in the linear code C L of length n over R, then the Lee weight enumerator of C L , Lee C L (z), is defined by Lee C L (z) = 2n j=0 A j z j . Through different choices of the defining set L, and particularly when F q is either the binary field (F 2 ) or a prime field (F p ), several optimal or nearly optimal codes from trace codes of the form C L where recently found ( [4,5,8,9,[11][12][13][14][15][16]). Particularly, the construction of two or few-weight codes from trace codes over the ring F q + uF q , was recently presented in [4].…”
Section: Introductionmentioning
confidence: 99%
“…For such construction, the defining sets for the trace codes are given in terms of cyclotomic classes, and for some of these classes, it is shown that it is possible to obtain the Lee weight distributions of the corresponding trace codes. Motivated by this construction, and by the p-ary semiprimitive irreducible cyclic codes over a prime field F p , the Lee weight distributions of an infinite family of p-ary three-weight codes from trace codes over the ring F p + uF p , was recently constructed in [11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations